Whole Ukrainian Scientific and Practical Conference “Archaeological Research of the Recent Years in Cherkasy Oblast: Results and Perspectives” (Археологія, 2023)
At the Bohdan Khmelnytskyi Cherkasy National University, on May 16—17, 2023, the Whole Ukrainian Scientific and Practical Conference “Archaeological research in of the recent years in Cherkasy region: results and perspectives” was held.